Pathological brain lesions in girls with central precocious puberty at initial diagnosis in Southern Vietnam - Quynh Thi Vu Huynh; Ban Tran Ho; Nguyen Quoc Khanh Le; Tung Huu Trinh; Luu Ho Thanh Lam; Ngan Thi Kim Nguyen; Shih-Yi Huang (Annals of Pediatric Endocrinology & Metabolism, 2022)
Purpose Cranial magnetic resonance imaging (MRI) is recommended to identify intracranial lesions in girls with central precocious puberty (CPP). Yet, the use of routine MRI scans in girls with CPP is still debatable, as pathological findings in girls 6 years of age or older with CPP are limited. Therefore, we aimed to identify the prevalence of brain lessons in CPP patients stratified by age group (0–2, 2–6, and 6–8 years). Methods This retrospective cross-sectional study recruited 257 girls diagnosed with CPP for 6 years (2010–2016). MRI was used to detect brain abnormalities. Levels of luteinizing hormone, follicle-stimulating hormone, and sex hormones in blood samples were measured. Results Most girls had no brain lesions (82.9%, n=213), and of the minor proportion of girls with CPP that exhibited brain lesions (17.1%, n=44), 32 girls had organic CPP. Pathological findings were detected in 33.3% (2 of 6) of girls aged 0–2 years, 15.6% (5 of 32) of girls aged 2–6 years, and 3.6% (8 of 219) of girls aged 6–8 years. Hypothalamic hamartoma and tumors in the pituitary stalk were the most common pathological findings. The likelihood of brain lesions decreased with age. Girls with organic CPP were more likely to be younger (6.1±2.4 vs. 7.3±1.3 years, P<0.01) than girls with idiopathic CPP. Conclusions Older girls appeared to have a lower prevalence of organic CPP. Clinicians should cautiously use cranial MRI for girls aged 6–8 years with CPP.